UTILITARIAN PERCEPTIONABOUT EWOM PLATFORMS AND CUSTOMERS' PURCHASE DECISION - Tariyal, Amit; Bisht, Swati; Chopra, Gaurav; Pratap, Sumit; Sharma, Megha (The journal of contemporary issues in business and government, 2021)
The eWOM platforms in today's world have become an essential source of information for every individual. However, customers perceive the eWOM platform usefulness based on the quality of information available in the platform. The present study attempts to apprehend the utilitarianperception about the eWOM platforms and the subsequent decision making for the hotelproducts and services. We propose a conceptual model and empiricallyverifyit using sample data of 338 respondents who had already experienced eWOM platforms. The study indicates that utilitarian aspectsof the eWOM platform influence the perceived usefulness (PU) of the eWOM platforms. It is also found that the customers' purchase decision (PD) related to the hotel's products and services is affected by the PU of eWOM platforms. Furthermore, the study also shows that acceptance of the eWOM platform and subsequent PD is influenced by gender.